Detailing evolved star wind complexity: comparing maser and thermal imaging. Issue Volume 16:Issue S366(2020) (November 2020) - Richards, A.M.S.; Assaf, K.A.; Baudry, A.; Decin, L.; Etoka, S.; Gray, M.D.; Pimpanuwat, B.
Abstract: Maser properties can be measured with milli-arcsec precision over multiple epochs using ALMA, cm- and mm-wave VLBI and e-MERLIN. This allows: (i) Tracing SiO maser proper motions in the pulsation-dominated zone; (ii) Quantifying clumpiness, variability and asymmetry of the wind traced by masers; (iii) Contrasting behaviour from OH masers even at similar distances from the star; (iv) Measuring magnetic fields. Mass lost from the star, traced by SiO masers, is likely to take decades to reach ∼5 stellar radii. At 5–50 stellar radii, once dust is well formed, 22-GHz H2 O masers show the wind accelerating through the escape velocity; its overall direction is away from the star but the velocity field is complex. In a few cases (so far), highly-directed, localised ejecta are seen. Magnetic fields appear to be stellar-centred and strong enough to influence wind kinematics. Recent ALMA and other observations have shown that otherwise inconspicuous companions shape a majority of evolved star winds, whilst advanced models demonstrate how, for some situations, this is compatible with masers showing negligible rotation proper motions. The long-term monitoring achievable at radio frequencies complements the multi-transition maser studies and analysis of thermal lines and dust at shorter wavelengths.